New genetic variations discovered in KRAS wild‐type cetuximab resistant chinese colorectal cancer patients. Issue 5 (5th March 2020) - Jing, Changwen; Wang, Ting; Ma, Rong; Cao, Haixia; Wang, Zhuo; Liu, Siwen; Chen, Dan; Zhang, Junying; Wu, Yang; Zhang, Yuan; Wu, Jianzhong; Feng, Jifeng
Abstract: To perform a comprehensive genomic analysis of colorectal cancer (CRC) tumor to detect genetic variants and identify novel resistant mutations associated with cetuximab‐resistance in CRC patients. A retrospective study was performed using whole exome sequencing (WES) to identify common genetic factors from 22 cetuximab‐sensitive and 10 cetuximab‐resistant patients. In all 10 cetuximab‐resistant patients, we discovered there are 37 significantly mutated genes (SMGs). CYP4A11 was the most frequently mutated gene in cetuximab‐resistant patients. BCAS1 and GOLGA6L1 were found to be among the second group of frequently mutated genes with a frequency of 60%. After cosine similarity analysis, three mutational signatures (signature a, b, and c) were found in all CRC tumors, similar to signature 1, 5, and 6 in COSMIC, respectively. Gene ontology analysis was performed on SMGs and found 12 enriched GO terms. Four genes are enriched in six specific Kyoto Encyclopedia of Genes and Genomes pathway groups, including the metabolism of xenobiotics by cytochrome P450, steroid hormone biosynthesis, retinol metabolism, and drug metabolism. Our data supports a network composed of SMGs and cellular signaling pathways that have been positively linked to the mechanisms of cetuximab resistance. These involve DNA damage repair, angiogenesis, invasion, drug metabolism, and the CRC tumor microenvironment. There is a SMG, OR9G1 correlated with survival rates of KRAS wild‐type colon adenocarcinoma patients. These findings support further investigation using WES in a prospective clinical study of cetuximab resistance CRC, to further identify, confirm, and extend the clinical significance of these and other potentially important new candidate predictive biomarkers of cetuximab response.